A Cross-Sectional Study Comparing Case Scenarios and Record Review to Measure Quality of Integrated Community Case Management Care in Western Uganda - Miller, James S.; Mbusa, Rapheal Kisolhu; Baguma, Stephen; Patel, Palka; Matte, Michael; Ntaro, Moses; Wesuta, Andrew Christopher; Mumbere, Nobert; Bwambale, Shem; McCarthy, Sara Mian; Kenney, Jessica; Guiles, Daniel; et al. (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2021)
In Integrated Community Case Management (iCCM), village health workers (VHW) assess and treat malaria, pneumonia and diarrhea using a clinical algorithm. Study objectives included: 1) Compare VHWs’ performance on case scenario exercises to record review data; 2) assess impact of formal education on performance in the case scenario exercises.36 VHWs in Bugoye Subcounty, Uganda completed the case scenarios exercise, which included video case scenarios and brief oral case vignettes, between July 2017 and February 2018. We obtained clinical records for all iCCM encounters in the same time period.In the video case scenarios, 45% of mock patients received all correct management steps (including all recommended education), while 94% received all critical management steps. Based on the level of data available from record review, 74% of patients in the record review dataset received overall correct management compared to 94% in the video case scenarios. In the case scenarios, VHWs with primary school education performed similarly to those with some or all secondary school education.The case scenarios produced higher estimates of quality of care than record review. VHWs often omitted recommended health education topics in the case scenarios. Level of formal education did not appear to influence performance in the case scenarios.
Keywords: community health workers, education level, educational status, Integrated Community Case Management, quality of health care, village health workers